Direct Evidence of the Lower Atmosphere Perturbations Producing Abnormal Ionospheric Longitudinal Gradients During Quiescent Geomagnetic Conditions - Yuyan Jin; Biqiang Zhao; Xu Zhou; Honglian Hao; Guozhu Li; Xinan Yue; Zishen Li (Geophysical Research Letters)
Abstract An unusual case of a large ionospheric longitudinal gradient in East Asia on 11 May 2021 occurred during a geomagnetically‐quiet period. It shows the largest east‐west difference in electron density at Yamagawa and Wuhan stations when Kp < 2 for 13:00–17:00 LT in 2021. Ground‐ and satellite‐based observations consistently confirm that there was a decrease in the west and an increase in the east of ∼125°E, with hemispherical symmetric with respect to the geomagnetic equator. The potential mechanism is further investigated through multi‐observations of plasma drifts and neutral winds, provided by the Ionospheric Connections Explorer satellite and newly‐established Sanya Incoherent Scatter Radar. The prominent longitudinal gradient in plasma drifts, electro‐dynamically coupled with E‐region winds, is suggested as the contributor for the east‐west differences, together with the strong gradient of F‐region winds in phase. This study provides direct evidence linking atmosphere perturbations to unusual longitudinal structure of terrestrial space plasma environment.